A comparison of the cleaning efficacy of ProRinse® syringe needle, ProUltra® PiezoFlow TM , and EndoActivator® irrigation techniques using software program ImageJ - Mohammed Al-Obaida; Mohammed Al-Ahmari; Nassr Al-Maflehi (Wolters Kluwer Medknow Publications, 2015)
The purpose of this ex vivo study was to evaluate the efficacy of three different irrigation techniques, ProRinse® syringe needle, ProUltra® PiezoFlow TM , and EndoActivator®, in cleaning the canals and isthmuses of human mandibular molars using a software program ImageJ. Materials and Methods : A custom-made metal cube was used to create a sealed canal system. Eighty extracted mandibular molars were randomly divided into four equal groups. Teeth were mounted; sectioned at 2, 4, and 6 mm; and reassembled into the metal cube. Chemo-mechanical preparation was done for all teeth. The teeth were divided into four groups for final debridement: Group 1 (control group) received only needle irrigation, group 2 used the ProRinse® syringe needle with 5% NaOCl irrigation within a 1-mm working length, group 3 used ProUltra® PiezoFlow TM ultrasonic agitation for 30 seconds, and group 4 used the EndoActivator® system to agitate for 30 seconds. All groups received a final irrigation with 5% NaOCl in each canal. Specimens were evaluated by digital image capture with a stereomicroscope. Statistical analysis was completed using an ANOVA test and Tukey's test. Results: The results showed no statistically significant difference in canal or isthmus cleanliness between the four groups. However, there was a statistically significant difference (P < 0.05) in isthmus cleanliness in group 4 at the 4-mm level. Conclusions: EndoActivator® produced a good result in isthmus cleaning at the 4-mm level.